Allium cyrilli (Amaryllidaceae): typification, taxonomy and update of the Italian distribution - Peruzzi, Lorenzo; Adorni, Michele; Dura, Teodoro; Ghillani, Luigi; Pasquali, Giancarlo; Rignanese, Luigi; Ronconi, Daniele; Teruzzi, Maurizio (Phytotaxa, 2012)
Allium cyrilli was long misinterpreted by Italian botanists and often confused with other taxa. In order to fix the application of this name, a lectotype is selected. The taxonomy of this species is clarified and discussed, especially in relation to the similar A. nigrum. Moreover, the distribution data of A. cyrilli in Italy are significantly updated, since the species is newly recorded for northern Italy (Piedmont, Emilia-Romagna and Veneto). The most useful qualitative and quantitative morphological characters, aimed to distinguish this species, are highlighted.